PENGUATAN PENDIDIKAN KARAKTER PESERTA DIDIK BERBASIS BUDAYA DISIPLIN DALAM PEMBELAJARAN PPKN KELAS X SMA NEGERI 2 KOTA TERNATE - Mohtar Kamisi; Mukhtar Yusuf (Jurnal Geocivic, 2022)
This study focuses on three main problems, namely (1) how the history of the "Sopik" ritual is carried out, (2) how the "Sopik" ritual is a customary law and (3) how the social values and cultural meanings are contained in the "Sopik" ritual. The research was conducted to reveal the history, social values, and cultural meanings contained in the “Sopik” ritual in Tahane, South Halmahera. The method used in this research is a qualitative method through two stages: (1) analyzing the results of interviews with informants from an emic and etic perspective and (2) interpreting the meaning and implications of the "Sopik" ritual.The results showed that (1) the ritual ceremony "Sopik" in the village of Tahane, Makean island is hereditary and is a manifestation of the interaction between Islamic culture and local culture. The traditional ritual ceremony of "Sopik" in Tahane village has long historical roots and is still preserved by the community. (2) the "Sopik" ritual was practiced in the beginning, there were disputes between the community members about village boundaries that could not be resolved. There have been many solutions taken by village leaders, but also no final decision has been reached. Traditional and religious leaders perform traditional oaths known as the "Sopik" ritual as a custom for resolving disputes between members of the community for generations, (3) the "Sopik" ritual has social values and cultural meanings, including: strengthening a consistent attitude towards mutual agreement, social glue, ethics and morals, customary law and deliberation and consensus.Keywords: Reciprocal Learning Model, Students, Learning Outcomes